2016
DOI: 10.2399/jmu.2016003006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing in patients with psoriasis considering the disease severity

Abstract: Psoriasis is a chronic inflammatory immune-mediated skin disease accompanied by various disorders. [1] Although the exact cause remains unknown, it is clear that both genetic and environmental factors play a role in these possible associations. The more common comorbidities include psoriatic arthritis, inflammatory bowel disease, cardiovascular diseases, hypertension, obesity, diabetes, and dyslipidemia which are thought to be the results of chronic inflammation in patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Temel et al 13 found that SNHL at high frequencies was significantly higher in psoriasis patients than in the control group. Hapa et al 18 reported that hearing thresholds at all frequencies were significantly higher in psoriasis patients compared to the control group. There are studies showing that psoriasis is associated with increased hearing loss by PTA, transient evoked otoacoustic emission (TEOAE) and DPOAE tests 7,10,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temel et al 13 found that SNHL at high frequencies was significantly higher in psoriasis patients than in the control group. Hapa et al 18 reported that hearing thresholds at all frequencies were significantly higher in psoriasis patients compared to the control group. There are studies showing that psoriasis is associated with increased hearing loss by PTA, transient evoked otoacoustic emission (TEOAE) and DPOAE tests 7,10,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of joint involvement in patients with psoriasis may cause a more chronic inflammatory process and may adversely affect hearing. While the studies 7,9,10,13,18‐20 evaluating the hearing of patients with psoriasis have different results, the hearing has been reported to be negatively affected in all of the studies 6,8,12 evaluating hearing in patients with psoriatic arthritis. These results support our theory.…”
Section: Discussionmentioning
confidence: 99%
“…When all clinical studies are reviewed, it has been observed that psoriasis/ PsA patients and the control group consisting of volunteer healthy subjects were compared with each other in terms of audiological changes [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In just a few studies, these groups were also evaluated in terms of the accompanying vestibular system involvement [15,20,21,25].…”
Section: Audiological/audiovestibular Evaluations In Patients With Psmentioning
confidence: 99%
“…Although non-specific erythematous, scaly and dry lesions are sometimes seen in the ear, the precise diagnosis of ear psoriasis can be made easily by detecting typical psoriatic lesions in other areas of the body [2,11]. Despite the high prevalence of clinical lesions affecting the auricle and the external auditory canal in psoriasis, there are not many studies evaluating the possible effect of psoriatic disease on the auditory system [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The auricle and outer one-third of the external auditory canal contain elastic cartilage covered with skin and its appendages, including mainly hair cells, and sebaceous and apocrine glands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation